2017
DOI: 10.1097/won.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Susceptibility, and Clonal Diversity of Pseudomonas aeruginosa in Chronic Wounds

Abstract: P. aeruginosa was present in 75% of tested chronic wound samples, and the same clones persisted for more than 1 month. In addition, most bacteria contained virulence genes that were associated with high potential to establish infection. The use of silver in chronic wounds may be associated with multidrug resistance in P. aeruginosa; therefore, it is important to avoid colonization by these bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
2
17
0
4
Order By: Relevance
“…First, diabetic patients can have higher levels of serum lactate due to diabetic ketoacidosis, and secondly, lactate is associated with wound bed colonization by bacteria which produce it as a byproduct 86 88 . > 80% of chronic wounds are colonized by P. aeruginosa 89 while 90% of chronic leg ulcers are colonized by S. aureus 78 , 90 93 which displays a cCCR phenotype 94 , 95 . Not surprisingly, these bacteria are often co-isolated 55 , 85 , 96 .…”
Section: Discussionmentioning
confidence: 99%
“…First, diabetic patients can have higher levels of serum lactate due to diabetic ketoacidosis, and secondly, lactate is associated with wound bed colonization by bacteria which produce it as a byproduct 86 88 . > 80% of chronic wounds are colonized by P. aeruginosa 89 while 90% of chronic leg ulcers are colonized by S. aureus 78 , 90 93 which displays a cCCR phenotype 94 , 95 . Not surprisingly, these bacteria are often co-isolated 55 , 85 , 96 .…”
Section: Discussionmentioning
confidence: 99%
“…PA infection is a common occurrence in chronic wounds [ 71 ] and is more fatal than other bacterial infections if left undetected or inappropriately treated [ 72 ]. In this study, we show that fluorescence imaging can rapidly detect PA in chronic wounds.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%
“…The identification of MRSA strains among patients from this study who were under ambulatory follow‐up care at a health unit located within a large hospital complex indicates a need to implement precautionary measures of contact in outpatient clinics to minimise the risks of cross‐contamination by multidrug‐resistant microorganisms. The results of previous studies indicated the non‐occurrence of this type of contamination in the units where this study was performed . However, periodic reassessments are warranted because selection pressure to generate multidrug‐resistant microorganisms increases proportionately with time and as the use of new commercially available antimicrobials increases.…”
Section: Discussionmentioning
confidence: 83%